Mechanism of progesterone promoting uterine smooth muscle contraction through RhoA/ROCK signaling pathway - YAN Xiaoli; CHEN Cheng; WANG Dan; CHANG Qing (陆军军医大学学报, 2022)
Objective To investigate the mechanism of progesterone affecting the contractions of uterine smooth muscle through RhoA/ROCK signaling pathway. Methods The tissues of uterine smooth muscle were collected from 5 cases in labor and another 5 of non-labor, respectively. The expression levels of phosphorylation of myosin light chain (p-MLC20), ROCK1 and ROCK2 were detected by Western blotting and immunohistochemical (IHC) assay. Uterine smooth muscle cells were isolated and cultured, and then identified by immunofluorescence assay. Laser confocal microscopy was used to measure the concentration of intracellular free Ca2+ ([Ca2+]i) in the cells. In addition, the uterine smooth muscle cells were treated with progesterone+progesterone receptor antagonist, mifepristone, and with progesterone+ROCK inhibitor, Y-27632, respectively. Western blotting was performed to determine the expression of p-MLC20, ROCK1 and ROCK2 in the corresponding groups. Results As compared with the non-labor group, the expression of p-MLC20, ROCK1 and ROCK2 in the uterine smooth muscle tissues were significantly increased in the labor group (P < 0.05). Progesterone induced the elevation of p-MLC20, ROCK1 and ROCK2 levels in the cultured uterine smooth muscle cells (P < 0.05), while after the intervention of Y-27632+progesterone, the p-MLC20 level was greatly decreased (P < 0.05). Conclusion Progesterone regulates p-MLC20 level through RhoA/ROCK signaling pathway and thus promotes the contractions of uterine smooth muscle cells.